Validación del proceso de manufactura de alkoyodo espuma (povidona yodada 7,5 %) en laboratorios Alkofarma e.i.r.l. - Chacaltana Lozano, Carlo Andre (2017)
The present work aimed to validate the manufacturing process of the Alkoyodo Foam product (povidone iodine 7.5%) in the Alkofarma E.I.R.L. laboratory facilities, for which the consecutive batches F1110426, F1120436 and F1120486 of Alkoyodo Foam were used in the presentation of 1000 mL, this being a concurrent validation; Taking into account parameters such as linearity, accuracy and precision and robustness in the manufacturing and packaging stages, in turn comply with the parameters of USP 39; The process capacity for each test for each stage (manufacturing and packaging) was also calculated. At the manufacturing stage, lots F1110426, F1120486 were the least dispersed in terms of linearity, accuracy and precision, with results of  (0.005), CV (%) (0.097%), Cp (46.81) and  (0.007), CV (%) (0.856%), Cp (5.96) for the average pH and average titration assays respectively. On the other hand, lots F1110426, F1120436 in the packaging stage were the ones that show less dispersed results in terms of linearity, accuracy and precision, since their standard deviation and coefficient of variation for the tests of average volume, average pH and mean values were  (0.041), CV (%) (0.004%), Cp (8.16);  (0.009), CV (%) (0.155%), Cp (28.21) and  (0.008), CV (%) (0.956%), Cp (5.35), batch problems met the organoleptic characteristics And microbiological tests. The validation is thus completed in a satisfactory manner, complying with all the parameters established by USP 39